The effectiveness of sports massage and cupping against heart rate changes and lactic acid after high-intensity interval training in athletes - Sifaq, Aghus; Nurhasan; Wahjuni, Endang Sri; Hariyanto, Agus; Muhammad, Heryanto Nur; Graha, Ali Satia; Rohman, Moh. Fathur; Setijono, Hari; Wijaya, Fransisca Januarumi Marhaendra; Pranoto, Adi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
Sports massage and cupping are ubiquitous in elite sports and increasingly common at the amateur level but evidence of these interventions has been underreported. The study's aim was to examine the effect of sports massage and cupping on changes in heart rate and lactic acid after high-intensity interval training (HIIT). This study utilized a quasi-experimental design with three experimental groups (sports massage group, cupping group, and sports massage plus cupping group) and one control group. A total of 40 athletes from East Java, Indonesia, participated. All groups consisted of ten athletes. The results showed that the sports massage intervention was more effective in reducing lactic acid and heart rate than the cupping group, the sports massage plus cupping group, and the control group. The results also indicated that the sports massage and cupping group had the lowest lactic acid and heart rate compared to the other groups (p ≤ 0.001). This study proves that sports massage and cupping was effective to reduce lactic acid and heart rate after high-intensity interval training. Our findings may contribute to helping guide coaches and athletes about the benefits of sports massage and cupping and provide information for incorporating sports massage and cupping into training and competition.